Profitabilitas, Financial Leverage, dan Cash Holding terhadap Perataan Laba dengan Good Corporate Governance sebagai Variabel Moderasi - Milasari, Anis; Maryanti, Eny (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2024)
Income smoothing is one of the earnings management techniques to manage company profits. There are several phenomena regarding income smoothing carried out by several companies in Indonesia. This research develops from previous research by adding one variable, namely profitability. This research used binary logistic regression methods and Moderated Regression Analysis (MRA). Data is taken from annual reports in food and beverage companies. The results of this study indicate that profitability has a positive effect on income smoothing, financial leverage has a negative effect on income smoothing, cash holding has no effect on income smoothing. The moderation results show that good corporate governance moderates the effect of profitability and financial leverage on income smoothing, but good corporate governance does not moderate the effect of cash holding on income smoothing. The results of this study are expected to be useful for further research and as a consideration for decision making for investors.